Social work interventions with survivors of acts of political violence. (March 2021) - Schiff, Miriam; Lesser, Lior; Levine, Tova; Savo, Yaeliy; Dashti, Tzlil; Rosenne, Hadas
Summary: Social workers and students in a large teaching hospital explored the characteristics of psychosocial interventions during acts of political violence. The associations between hospital length of stay, Acute Stress Reaction, and the characteristics of the implemented psychosocial interventions were also examined. One hundred and forty patients (61.4% males) treated during the so-called stabbing intifada/uprising in the years 2014–2015 in Israel in one large hospital were included. Data collection was based on clinical data mining. Findings: The most frequent patient interventions were trauma-focused, while the most frequent family interventions were needs assessment and support-system building. Most of the interventions with the family (but not with the patient) were associated with longer hospital stays. Greater severity of Acute Stress Reaction was associated with greater use of trauma-focused interventions with the patient (but not with the family). Applications: The findings suggest that social workers hold implicit trauma-focused intervention theories that should be written up in order to develop practice-based intervention models in the context of political violence.